ALOE VERA BARBADENSIS MILLER AS AN ALTERNATIVE TREATMENT FOR CHILDREN WITH FEVER - Siti Choirul Dwi Astuti; Suhartono Suhartono; Ngadiyono Ngadiyono; Supriyana Supriyana (Belitung Raya Foundation, Indonesia, 2017)
Background: Applying a cooling treatment from outside the body is one way to lower fever in children. Midwives commonly perform a warm water compress in their care, but it is considered less effective. Thus, compress with Aloe Vera Barbadensis Miller is proposed in this study as an alternative treatment. Objective: To examine the effect of Aloe Vera Barbadensis Miller compress in reducing body temperature in children with fever. Methods: This was a quasi-experimental study with pretest and posttest with control group design. Forty children were recruited, with twenty of them assigned in each group. Purposive sampling was performed to select the sample. A digital rectal thermometer was used to measure the temperature. Independent t- test and paired test were used for data analysis. Results: Findings showed that the Aloe Vera compress group showed a higher decrease of body temperature compared to the warm water compress group. The difference of body temperature after 20 minutes in the experiment group was 1.435 while in the control group was only 1.085. There were statistically significant differences in body temperature between the experiment and control group (p=0.013). Conclusion: Aloe Vera Barbadensis Miller compress is an effective alternative therapy in reducing body temperature in children with fever. It is recommended for midwives to apply this intervention to reduce body temperature significantly.